New data on the distribution of the 'deep-sea' sponges Asbestopluma hypogea and Oopsacas minuta in the Mediterranean Sea - Bakran-Petricioli, T.; Vacelet, J.; Zibrowius, H.; Petricioli, D.; Chevaldonné, P.; Raa, T. (Marine Ecology, 2007)
The sponges Oopsacas minuta (Hexactinellida) and Asbestopluma hypogea (Demospongiae, Cladorhizidae) belong to groups that are typical of deep water, but both species have already been recorded from the shallow water Trois Pépés cave at La Ciotat (Marseille area). We here report on subsequent findings of A. hypogea in two other littoral caves: one at Garmenjak Island in the Middle Adriatic (Croatia), the other at Jarre Island (Marseille, France). The maximum temperatures experienced in situ by these populations are not only significantly higher than those from the deep Mediterranean Sea, but they are also up to 6°C higher than those reported for the Trois Pépés cave population, up to 23.1°C in July 2002 for the Garmenjak population and 22.8°C in August 2004 for the Jarre population (exposures from a few hours to a few days). The average summer temperature inside both caves remains several degrees lower than the outside temperature at the same depth. Long-term survival of A. hypogea populations at the relatively high summer/autumn temperatures in both Jarre cave (4 years monitoring) and Garmenjak cave (5 years monitoring) indicates that the species can successfully colonise such shallow habitats in spite of its presumed deep-water origin. We also report additional cave records of O. minuta in the Adriatic (Croatia): from the marine part of the Z ? iva Voda anchialine cave at Hvar Island, from the marine caves at Is?ki Mrtovnjak, Lastovo and Fras?keric´ Islands. The wide distribution of this species in the deep Mediterranean is substantiated by a record on Santa Lucia Bank north of Corsica (303 m) and photographs taken by the submersible Cyana in the Central Tyrrhenian Sea (2912 m, 2845 m) and the Ionian Sea (2447 m). All the findings of these two species in the Mediterranean are reviewed and possible patterns of their colonisation of littoral caves are discussed.